Identifying Binding Constraints to Growth : Does Firm Size Matter? - Vargas, Mauricio (IMF Working Papers; Working Paper ;, 2015)
As emphasized by Hausmann, Rodrik and Velasco, the policy challenge of boosting growth requires prioritization and identifying what are the most binding constraints. This paper draws on firm-level data from the World Bank Enterprise Survey, which suggests that the obstacles for the functioning of firms is related to firm size. Recognizing the potential endogeneity and simultaneity between firms' constraints and firm size, we implement an Ordered-Probit model with a potential categorical endogenous regressor to estimate, for the case of Bolivia, the conditional probability of facing obstacles given the firm size category, while controlling for other factors. The results confirm the importance of allowing for the roles of firm size in identifying constraints and suggest priorities for policies to remove constraints to economic performance.